Perioperative interruption of direct oral anticoagulants and vitamin K antagonists in patients with atrial fibrillation: A comparative analysis - Shaw, Joseph R. (Res Pract Thromb Haemost, 2020)
BACKGROUND: There is a paucity of studies comparing postoperative thromboembolic and major bleeding complications following perioperative interruption of the direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs). OBJECTIVE/METHODS: We conducted a retrospective cohort study to compare postoperative thromboembolic and major bleeding outcomes following perioperative interruption of DOACs and VKAs in patients with atrial fibrillation. The primary efficacy and safety outcomes were the 30‐day postoperative rates of arterial thromboembolic events (ATEs) and major bleeding, respectively. The secondary outcomes included the 30‐day rates of clinically relevant nonmajor bleeding (CRNMB) and overall mortality. Thromboembolic, major bleeding, and mortality outcomes were independently adjudicated. Multivariable mixed‐effects logistic‐regression models were used to adjust for potential confounding variables between the DOAC and VKA cohorts. RESULTS: A total of 325 DOAC patients undergoing 351 procedures and 199 VKA patients undergoing 221 procedures were included. The 30‐day ATE rate was 0.57% (95% confidence interval [CI], 0.27‐0.8) in the DOAC cohort. There were no ATEs in the VKA cohort. The 30‐day rates of major bleeding were 0.57% (95% CI, 0.27‐0.8) and 3.62% (95% CI, 0‐7.3) in the DOAC and the VKA cohorts, respectively. There were significantly more postoperative major bleeding events in the VKA cohort. The 30‐day rate of CRNMB was 4.27% (95% CI, 4.15‐4.42) in the DOAC cohort and 4.52% (95% CI, 3.67‐5.38) in the VKA cohort. There were 2 deaths in the VKA cohort, one of which was deemed to be a fatal nonsurgical bleeding event. CONCLUSIONS: The perioperative interruption of VKAs may be associated with higher postoperative major bleeding rates as compared to DOACs. Careful postoperative reinitiation and monitoring of VKA anticoagulation may be warranted following surgical procedures.